Estimated surface area and volume of the term new-born indices of neonatal survival - Flores, John Vincent Policarpio G.
In spite of the decreasing infant mortality ratio noted worldwide, the proportion of infant deaths attributed to the neonatal period was observed to be on the rise. Hence, the use of anthropometry at birth was endorsed by the World Health Organization for the purpose of screening for new-borns at higher risk of neonatal mortality. In this regard, a retrospective cohort study was conducted relating the body surface area and body volume with neonatal mortality. Secondary anthropometric and socio-demographic data from the study of Flores in 1992 were applied in the study. The data set comprised 1984 Mother-Infant pairs recruited from 14 Lying-in Clinics in Manila. The surface area and the volume of the new-bron were estimated using three body configurations each. These geometric figures include the sphere, the cylinder, the cone and the frustum of a cone. Known mathematical formulae of the geometric figures were used in the computation of the geometric indices. Logistic regression modeling and stratified analyses were employed to appraise the relationship between the geometric indices and neonatal mortality with simultaneous control of confounding as well as to detect effect modification. Results showed that these geometric indices were significant predictors of neonatal mortality controlling for the effects of maternal nutrition, maternal education, parity, type of feeding during the neonatal period, monthly household income, number of prenatal visits, family house condition and environmental sanitation. The sensitivity, specificity and accuracy of the six geometric indices in predicting neonatal mortality were pegged between 70-71. The body surface area and the body volume were likewise found to be very highly correlated with birth weight. Recommendations of the study included the diagnostic use of the body volume following one of the body configurations for purposes of identifying new-borns at higher risk of neonatal death in a scenario where birth weight determination is not feasible. The study likewise devised a handy instrument that can facilitate determination of body volume using the birth length, head, chest, mid-upper arm and thigh circumferences.